Mercy land [videorecording (DVD)] - Rickards, Simon; Learmonth, Celia; Clarke, Olivia; Silver, Ben (Octane Multimedia, 2025)
Living alone in a desolate future Earth, a mother and daughter flee after their commune is destroyed by a vicious gang. Struggling against foes and the elements, their only hope is to travel the wasteland in hopes to uncover a hidden technology.